PENGARUH KOMITMEN PEGAWAI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI, USAHA KECIL MENENGAH DAN PERDAGANGAN KOTA PEMATANGSIANTAR - Mustika, Widya; Lie, Darwin; Efendi, Efendi; Inrawan, Ady (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The results of this study can summarized as follows: 1. Employee commitment is moderately high correlation, work discipline and employee performance are good. 2. The results of multiple linear regression indicate a positive influence between employee commitment and work discipline on employee performance. 3. The results of the analysis of the correlation coefficient have a moderately high and positive correlation between employee commitment, work discipline and employee performance at Dinas Koperasi, Usaha Kecil Menengah dan Perdagangan Pematangsiantar. 4. The hypothesis test results stated that H0 was rejected, meaning that employee commitment and work discipline had a positive and significant effect on the performance of employees at Dinas Koperasi, Usaha Kecil Menengah dan Perdagangan Pematangsiantar both simultaneously and partially.Keywords: Employee Commitment, Work Discipline, and Employee Performance